A feasibility study for rubber (Hevea brasiliensis) replanting at TSB Kampung Simat, Johol district Kuala Pilah, Negeri Sembilan, Malaysia - Mahusin, Muhammad (2015)
A study was conducted at TSB Kampong Simat, Johol, Negeri Sembilan to determine soil feasibility study for Hevea brasiliensis replanted in that area. The size of the study area was 60 hectares with 37 smallholders as land owners. The reading of GPS coordinate was from 2.5596° to 2.574° North and 102.265° to 102.28° East with elevation from the sea level was 125 meter to 160 meters. Terrains in this area were undulating to hilly. The distance of the study area from down town Kuala Pilah, Negeri Sembilan is around 30 km. The scale of study used was 1:50,000 (Semi-detail survey). The objectives of this study were: 1) To determine the land size (Ha) based on a reconnaissance soil survey of the soil types in TSB Kampung Simat, Johol District, Kuala Pilah, Negeri Sembilan for rubber replanting; 2) To determine soil the physic-chemical characteristics of the soil in the study area for rubber replanting; 3) To evaluate soil-crop suitability for rubber replanting in the study area. A total of 10 composite soil samples at a depth of 0 to 15 cm and 15 to 30 cm using screw auger were collected using the zigzag sampling method. The laboratory analyzes for the soil samples were conducted at Espek Research and Advisory Services, (ERAS) laboratory, located at Bangi Training Centre, Selangor. Soil analysis carried out to determine the physical and chemical properties of the soils. Two soil series were identified are Tai Tak Series (Pedon 1) and Rengam/r Series (Pedon 2). The colour of Tai Tak Series was identified from dark yellowish brown (10 YR 4/6), yellowish brown (10 YR 5/8) and brownish yellow (10 YR 6/8). The percentage of clay is 52 %, silt content of 16 % and sand content is 32 % in the subsoil texture. While Rengam/r Series, the colour was identified from strong brown (7.5 YR 5/6) to yellowish red (5 YR 5/8) shows high iron content in this soil. From the results, the pH value of the study area was lower than optimum pH required for the rubber growth. The increased of pH value was depended of the based saturation. The soil pH can effect of the CEC value. At very low pH value, the CEC was also generally lowed. Tai Tak series and Rengam/r Series were low CEC value less than 10 cmolc/kg soil. CEC is an important consideration not only for nutrients already present in the soils, but also for those applied in the fertilizers in other ways. The application of fertilizer for immatured rubber can used from RISDA recommended rate. Classification of soil series were adapted based on soil taxonomy, which is a USDA Soil Taxonomy System (Soil Survey Staff, 2010) and Malaysia Taxonomy System (Paramanathan, 2009). Tai Tak Series for this site fall into Class 2 in soil suitability classes with three moderate limitations of gradient, CEC and soil texture for rubber growth. Hence, Rengam/r Series fall into Class 3 in soil suitability classes with one serious limitation of gradient and two moderate limitations of CEC and texture for rubber growth in this site. However, with proper soil management practices and good agriculture practices for rubber cultivation, these soils have potential for optimum rubber production in the future.